Symposium on the role of religious leaders in peacemaking and social change in Africa: Zambia’s case - Sakala, F.D. (Acta Theologica, 1994)
The Zambian people chose a new president on 31 October 1991 after almost twenty years under one party rule. This action brought to an abrupt and unexpected end the rule of Dr Kenneth Kaunda and his United National Independence Party (UNIP) after twenty seven years in power. It was a humiliating defeat in that UNIP only got about 25 per cent of the popular vote. They managed to win only 20 seats out of the 150 parliamentary seats. The transition from a single to multi-party democracy was peaceful following the free and fair elections. This made Zambia an example of a new wave of democratization which is sweeping across Africa in this last decade of the twentieth century. This paper looks at the role of religious leaders in peacemaking and social change in Zambia. It also discusses how the Christian Church (Catholic and Protestant) has worked together on political and social issues in Zambia.